PENGARUH ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) DISCLOSURE TERHADAP KINERJA KEUANGAN DENGAN FINANCIAL SLACK SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2022-2024) - Savana Elga Felisha; Paulus Theodorus Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2026)
This research refers to previous studies that examine the influence of Environmental, Social, and Governance (ESG) disclosure on financial performance, which show inconsistent results. This research aims to examine the effect of ESG disclosure on financial performance measured by Tobin's Q. In addition, this research also examines the role of financial slack in moderating the relationship between ESG disclosure and financial performance. The variables used in this research are environmental, social, and governance disclosure as the independent variables, financial performance as the dependent variable, and financial slack as the moderating variable. The research also includes ROA, firm size, and leverage as control variables.Secondary data are used in this research and purposive sampling is applied as the sampling technique. The difference between this research and prior studies lies in the data source, sample coverage, and analytical method. This research focuses on manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2022–2024, with ESG data obtained from Bloomberg, resulting in 119 selected samples. Data are analyzed using Partial Least Squares – Structural Equation Modeling (PLS-SEM) with SmartPLS 3, including descriptive statistical analysis, measurement model (outer model) and structural model (inner model) evaluation, and hypothesis testing through bootstrapping.The results show that Environmental Disclosure has a positive and significant effect on Financial Performance. Social Disclosure and Governance Disclosure do not have a significant effect. Financial Slack does not moderate the effect of Environmental Disclosure, but it strengthens the effect of Social Disclosure, and weakens the effect of Governance Disclosure at a 10 percent significance level.